The complete chloroplast genome of Elaeagnus conferta Roxb (Elaeagnaceae) - Jin Liu; Li-Dan Gong; Lin Qi; Zi-Yan Liu; Ying-Feng Niu; Chao Shi (Mitochondrial DNA. Part B. Resources, 2019)
Elaeagnus conferta Roxb is a kind of fruit known for its oval shape, bright red colour, and sour and sweet taste. In this study, we assembled and characterized the complete chloroplast genome of E. conferta Roxb as a resource for future genetic studies. With a total length of 151,751 bp, the chloroplast genome has a total of 130 genes, consisting of 88 protein-coding genes, 34 tRNA genes, and 8 rRNA genes. Phylogenetic analysis confirmed the position of E. conferta Roxb within the order Rosales.